Pelatihan Optimalisasi Riset Dan Inovasi Akademik Mahasiswa Melalui Publikasi Artikel Terindeks Sinta 2 Sebagai Alternatif Pengganti Skripsi - Wenti Ayu Sunarjo; Siti Nurhayati (PT. Berkah Digital Teknologi, 2025)
The development of higher education policies in Indonesia has opened new opportunities for undergraduate students to complete their studies not only through theses but also through publications in nationally accredited journals, particularly SINTA 2-indexed journals. However, students’ limited understanding of the fundamental differences between theses and journal articles often becomes an obstacle in determining an effective and efficient final project strategy. This community service activity aims to provide conceptual and practical insights into the characteristics, structure, procedures, and writing strategies of theses and SINTA 2 journal articles as alternative graduation pathways. The method used was academic socialization through seminars and interactive discussions. The results indicate an increased understanding among students regarding structural differences, assessment orientation, and academic opportunities offered by scientific publications. This activity is expected to assist students in choosing an appropriate final project pathway based on their interests, competencies, and future academic prospects, while also fostering a culture of scientific publication in higher education institutions. ABSTRAK Perkembangan kebijakan pendidikan tinggi di Indonesia membuka peluang baru bagi mahasiswa untuk menyelesaikan studi sarjana tidak hanya melalui skripsi, tetapi juga melalui publikasi artikel ilmiah pada jurnal terakreditasi nasional, salah satunya jurnal terindeks SINTA 2. Namun demikian, minimnya pemahaman mahasiswa mengenai perbedaan mendasar antara skripsi dan artikel jurnal sering menjadi hambatan dalam menentukan strategi tugas akhir yang efektif dan efisien. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pemahaman konseptual dan praktis kepada mahasiswa mengenai karakteristik, sistematika, prosedur, serta strategi penyusunan skripsi dan artikel jurnal SINTA 2 sebagai alternatif kelulusan. Metode yang digunakan adalah penyuluhan akademik melalui seminar dan diskusi interaktif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman mahasiswa mengenai perbedaan struktur, orientasi penilaian, serta peluang akademik yang ditawarkan oleh publikasi ilmiah. Kegiatan ini diharapkan dapat membantu mahasiswa dalam menentukan jalur tugas akhir yang sesuai dengan minat, kemampuan, dan prospek akademik ke depan, serta mendorong budaya publikasi ilmiah di lingkungan perguruan tinggi.